GSK-3β inhibition confers cardioprotection associated with the restoration of mitochondrial function and suppression of endoplasmic reticulum stress in sevoflurane preconditioned rats following ischemia/reperfusion injury. (November 2018) - Wang, Yujia; Ge, Chunlin; Chen, Junfeng; Tang, Kun; Liu, Jianjun
Background: Sevoflurane has been shown to protect against myocardial ischemia/reperfusion (I/R) injury in animals, while its cardioprotection is lost if the ischemic insult is too long. In this study, we proposed a prevailing hypothesis that GSK-3β inhibitor-mediated activation of GSK-3β/β-catenin signaling pathway provides additional cardioprotection in sevoflurane preconditioned rats following I/R injury. Methods: Rats were subjected to treatment with TDZD-8, a GSK-3β inhibitor, 5 minutes prior to sevoflurane preconditioning and 30-minute ischemia and 120-minute reperfusion. Furthermore, in order to find out whether this cardioprotection is linked with mitochondrial function and endoplasmic reticulum stress (ERS), we isolated mitochondria from rat hearts perfused with TDZD-8 and determined the alternations of ERS markers. Results: Sevoflurane preconditioning or GSK-3β inhibitor treatment prevented cardiomyocyte apoptosis, phosphorylated GSK-3β and accelerated total β-catenin expression levels, reduced mitochondrial permeability transition pore (MPTP) activity, promoted the recovery of mitochondrial membrane potential and decreased the expression levels of GRP78, caspase-12 and C/EBP homology protein (CHOP) in rats under I/R condition, suggesting sevoflurane preconditioning or TDZD-8 activate the GSK-3β/β-catenin signaling pathway, improve mitochondria function and suppress ERS occurrence. Conclusions: Taken together, the findings obtained from the study support the concept that sevoflurane preconditioning confers cardioprotection against myocardial I/R injury and GSK-3β/β-catenin signaling activation mediated by TDZD-8 as a novel target to prolong cardioprotection by sevoflurane anaesthesia.